China and the credit crisis : the emergence of a new world order - Chance, Giles (J. Wiley & Sons (Asia), 2010)
The western world attributed China's role as world's largest financer of the developed world and third largest economy in the world to new economic efficiencies, a revolution in risk management and its own wise policies. China and the Credit Crisis argues that if the extent of the role played in the new prosperity by an emerging China, and the fundamental nature of the changes it brought had been better understood, more appropriate policies and actions would have been adopted at the time which could have avoided the crash, or at least limited its impact. China's Credit Crisis examines the larger role that China will play in the recovery from the current credit crisis and in the post-crisis world. It addresses the major questions which arise from the financial crisis and discuss the landscape of the post-credit crisis world, initially by continuing to provide growth to a world deep in recession, and later by sharing global economic and political leadership.